Calculation of the longitudinal electron scattering form factors for the 2s-1d shell nuclei - Hamoudi, A. K. (Iraqi Journal of Physics, 2011)
An Expression for the transition charge density is investigatedwhere the deformation in nuclear collective modes is taken intoconsideration besides the shell model transition density. Theinelastic longitudinal C2 and C4 form factors are calculated usingthis transition charge density for the Ne Mg 20 24 , , Si 28 and S 32nuclei. In this work, the core polarization transition density isevaluated by adopting the shape of Tassie model togther with thederived form of the ground state two-body charge densitydistributions (2BCDD's). It is noticed that the core polarizationeffects which represent the collective modes are essential inobtaining a remarkable agreement between the calculated inelasticlongitudinal F(q)'s and those of experimental data